Assessing Digital Competence and Inter-Area Correlation among Undergraduate Chemistry Education Students Using DigComp 3.0 - Putu Anindita Widhiya Putri; Adik Annisa; Arum Setyaningsih; Vella Aulia Illahi (Universitas Pendidikan Mandalika, 2026)
In order to mitigate hazards like misinformation and cybercrime, digital competence in the twenty-first century requires more than just frequent device use. Using the most recent DigComp 3.0 framework for 2025, this study aims to assess the digital competency profile of chemistry education students and assess its implications for future learning design. Eighty-eight chemistry students from Universitas Sebelas Maret and Universitas Negeri Malang were surveyed as part of a quantitative approach. A 22-item self-assessment tool encompassing five domains of digital proficiency was used to gather the data, which were then evaluated using descriptive statistics and the Spearman correlation test. The findings show that students reached advanced proficiency in Areas 1 (Information Search, Evaluation and Management), 2 (Collaboration and Communication), and 4 (Safety, Wellbeing, and Responsible Use), while Areas 3 (Content Creation) and 5 (Problem Identification and Solving) remained at the intermediate level. Most inter-area correlations were weak and positive, while the correlation between Areas 4 and 5 was moderate. In conclusion, students who are exposed to technology on a daily basis do not always become highly skilled in digital abilities. To enhance the capacity to produce digital chemistry material and resolve challenging technological issues in a college setting, certain educational interventions and training programs are therefore required.